Pelatihan Kewirausahaan Berbasis Pangan Lokal Untuk Memulai dan Mengembangkan Bumdes Duawutun, Kecamatan Nagawutung, Kabupaten Lembata - Wilbertus G. Britanye; Hilda Teli Sensa; Petrus Hyacintus R. Nau; Maria A. Bhiju; Maria I. Bau; Yohana Fransiska Medho; Yasinta Palan Peten (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This study examines the efforts of local food-based entrepreneurship training to start and develop BUMDesa Duawutun, Nagawutung, Lembata. This study is based on data from the 2021-2027 Duawutun RPJMDes, explaining the inhibiting factors for BUMDes management in Duawutun Village, namely the BUMDes management is not functioning properly, the lack of Human Resources (HR) for BUMDes management, and BUMDes still lacks funds, so that in 2023 the Duawutun Village Government will dissolve BUMDes Duawutun. The method used in this activity is socialization and practice with the aim of providing explanations and honing the skills of the Family Welfare Empowerment (PKK) mothers, BUMDes administrators, and the Duawutun Village community directly. This training activity produces several local products in the form of (cassava chips and pumpkin sticks). The main targets of this activity are BUMDes administrators and PKK mothers.